2015
DOI: 10.14260/jemds/2015/1129
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Glenoid Fossa of Scapula

Abstract: ABSTRACT:The study was conducted on sixty scapulae obtained from the department of Anatomy, Government Medical College, Jammu. The shape of the glenoid cavity was observed in all the scapulae. It was inverted comma shaped, tear drop shaped, oval and round shaped. The shape on the two sides was compared. Morphometry of the glenoid cavity was done and compared on right and left side. The dimensions of the glenoid fossa provide important information for designing and fitting of glenoid component for shoulder arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…The mean VD in this study was found to be larger on the right side. This confirmed the findings of This confirmed the findings of Dhinsda and Singh (2014), Mahto and Omar (2015), Gupta et al (2015) and Hassanein (2015). Although HD1 has only been investigated in a limited number of studies, the values of the current study were similar to the studies conducted by Mamatha et al (2011) and Chhabra et al (2015), where the mean HD1 was found to be larger on the right side (Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The mean VD in this study was found to be larger on the right side. This confirmed the findings of This confirmed the findings of Dhinsda and Singh (2014), Mahto and Omar (2015), Gupta et al (2015) and Hassanein (2015). Although HD1 has only been investigated in a limited number of studies, the values of the current study were similar to the studies conducted by Mamatha et al (2011) and Chhabra et al (2015), where the mean HD1 was found to be larger on the right side (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Although HD1 has only been investigated in a limited number of studies, the values of the current study were similar to the studies conducted by Mamatha et al (2011) and Chhabra et al (2015), where the mean HD1 was found to be larger on the right side (Table 4). The mean HD2 was also observed to be larger on the right side, agreeing with the reports of previous studies (Mamatha et al, 2011;Gupta et al, 2015;Hassanein, 2015;Mahto and Omar, 2015) (Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Left glenoid value was slightly higher than the right. In a study done by Gupta et al in north India the vertical diameter of glenoid fossa were 3.49cms and 3.30cms on right and left side [5]. Gamal et al studied 68 dry Egyptian scapulae and reported the mean of vertical diameter of glenoid fossa as 3.31cms on right side and 2.87cms on left side.…”
Section: Discussionmentioning
confidence: 96%